2019
DOI: 10.1177/0145482x19844078
|View full text |Cite
|
Sign up to set email alerts
|

Transporting People with Visual Impairments: Knowledge of University Campus Public Transportation Workers

Abstract: Introduction: To support independent travel skills and accessibility for people with visual impairments (i.e., those who are blind or have low vision), this research acknowledges bus driver perceptions of visual impairment and investigates how bus drivers interact with visually impaired travelers who ride public transportation. Methods: This study utilized the Social Responsibility about Blindness Scale and a researcher-created instrument to explore how bus drivers interact with visually impaired travelers. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Only two studies under the current review included drivers as participants (Abraham et al, 2021; Fast & Wild, 2019) as shown in Table 2. Fast and Wild (2019) reported that drivers had concerns about the failure of persons with visual disability to recognize the correct stops, locate a seat, and directionality to ensure their safety, as passengers are at risk of tripping or falling (Fast & Wild, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Only two studies under the current review included drivers as participants (Abraham et al, 2021; Fast & Wild, 2019) as shown in Table 2. Fast and Wild (2019) reported that drivers had concerns about the failure of persons with visual disability to recognize the correct stops, locate a seat, and directionality to ensure their safety, as passengers are at risk of tripping or falling (Fast & Wild, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Only two studies under the current review included drivers as participants (Abraham et al, 2021; Fast & Wild, 2019) as shown in Table 2. Fast and Wild (2019) reported that drivers had concerns about the failure of persons with visual disability to recognize the correct stops, locate a seat, and directionality to ensure their safety, as passengers are at risk of tripping or falling (Fast & Wild, 2019). The second study noted that drivers did not know how to relate to visually impaired pedestrians during public transport, they also did not have knowledge about the seating options for passengers with visual disability.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations